Teaching Presence in Asynchronous Online Classes: It’s Not Just a Façade - Sharon Watson; Daniel P. Sullivan; Kathryn Watson (Online Learning, 2023)
The expanding scale and scope of online education options, both in terms of design and delivery, creates significant questions that increasingly warrant research attention. This empirical study investigates students’ perceptions and evaluative judgments of a number of methods of setting and sustaining Instructor Presence in an online asynchronous course. Based on factor analysis of our data, we propose refining the idea of Instructor Presence in terms of stylistic versus substantive methods. Tests of student survey data indicate that, while students see value in both types of Instructor Presence, they perceive significantly greater benefit from substantive relative to stylistic methods.